Development of shearography for surface strain measurement of non-planar objects - Groves, Roger M. (Cranfield University, 2001)
The subject of this thesis is the development of optical instrumentation for surface strain measurement of non-planar objects. The speckle interferometry technique of shearography is used to perform quantitative measurements of surface strain on nonplanar objects and to compensate these measurements for the errors that are due to the shape and slope of the object. Shearography is an optical technique that is usually used for defect location and for qualitative strain characterisation. In this thesis a multi-component shearography system is described that can measure the six components of displacement gradient. From these measurements the surface strain can be fully characterised. For non-planar objects an error is introduced into the displacement gradient measurement due to the variation of the sensitivity vector across the field of view and the variation in the magnitude of applied shear due to the curvature of the object surface. To correct for these errors requires a knowledge of the slope and shape of the object. Shearography may also be used to measure object slope and shape by a source displacement technique. Therefore slope, shape and surface strain may be measured using the same optical system. The thesis describes a method of multiplexing the shear direction using polarisation switching, a method of measuring the source position using shadow Moire and the shearography source displacement technique for measuring the surface slope and shape of objects. The multi-component shearography system is used to perform measurements of the six components of surface strain, on an industrial component, with a correction applied for errors due to the shape and slope of the object.